Relaxation dynamics of liposomes in an aqueous solution. Issue 28 (28th July 2015) - Kundu, S. K.; Choe, S.; Sasaki, K.; Kita, R.; Shinyashiki, N.; Yagihara, S.
<x xml:space="preserve">Abstract</x> The gel–liquid crystal phase transition has been studied by the temperature and frequency dependent dielectric relaxation behavior of liposomes in an aqueous solution (40 g L−1 DPPC–water mixture).